THE EFFECT OF GENRE-BASED APPROACH TOWARDS STUDENTSâ WRITING COMPETENCY IN THE ELEVENTH GRADE STUDENTS OF SMA NEGERI 4 SINGARAJA IN ACADEMIC 2014/2015 - ., Ni Made Ayu Vinandari Safitri; ., Prof. Dr. Ni Nyoman Padmadewi,MA; ., Drs.Sudirman, M.L.S (Jurnal Pendidikan Bahasa Inggris, 2013)
This study was aimed at finding out whether there was significant difference in writing competency of eleventh grade students of SMA N 4 Singaraja between those who were taught using Genre-based Approach and those who were taught using Conventional Writing Strategy. The research was designed by using posttest only control group design. The population of this study was the students of class XI. There were two groups of samples in this research, which were selected by cluster random sampling. Class XI MIA 6 was assigned as the experimental group and treated by using Genre-Based Approach. Another class, XI MIA 5 was assigned as the control group and treated by using Conventional Writing Strategy. The treatments were conducted sixth times for each. At the end of the treatments period, the posttest was administrated. The result of posttest IS analyzed descriptively and inferentially. The result of this study showed that the experimental group performed better competency in writing rather than the control group. It was proven by the result of their posttest. The descriptive analysis shows that the mean score of experimental group 77.9 was higher than the control group 68.4. The inferential analysis also shows that t_o was 4.865. It was higher than the value t_cv at 1.99 (P = 0.05). It could also be seen that the significance value of the two tailed independent sample t-test (equal variance assumed) showed the value of 0.000 (less than 0.05). On the basic result of the study above, it can be concluded that the alternative hypothesis (Ha) used in this study was approved. It means that there was a significant difference in writing competency of grade eighth students of SMA N 4 Singaraja between those who were taught using Genre-Based Approach and those who were taught using Conventional Writing Strategy.Kata Kunci : Writing Competency and Genre-Based Approach Penelitian ini bertujuan untuk menemukan perbedaan pengaruh terhadap kemampuan menulis siswa di SMA N 4 Singaraja terhadap pengajaran mengunakan Genre-Based Approach dan strategi biasa. Penelitian ini di bentuk dengan menggunakan posttest only control group design. Populasi yang digunakan di penelitian ini adalah siswa kelas XI. Ada dua sample yang digunakan di penelitian ini, yang mana dipilih dengan cara cluster random sampling. Kelas XI MIA 6 dijadikan grup eksperimental dan XI MIA 5 dijadikan grup control. Masing-masing grup diajar selama 6 kali dan terkahir diberikan tes yang disebut posttest. Hasil dari posttest dianalis secara deskriptif dan inferensial. Hasil dari penelitian ini menunjukan grup eksperimental memiliki kemampuan menulis yang lebih baik. Ini ditunjukan dari hasil posttest. Analisis secara deskriptif menunjukan nilai rata-rata grup eksperimental adalah 77.9 dan grup kontrol 68.4. Analisis secara inferensial menunjukan t_o sebesar 4.865. itu lebih besar dari t_cv yg mana hanya 1.99 (P = 0.05). Ini juga bisa dilihat dalam pengaruh nilai dari two tailed independent sample t-test (equal variance assumed) menunjukan nilainya adalah 0.000 (lebih sedikit dari 0.05). Hasil diatas menunjukan bahwa alternative hypothesis (Ha) dalam penelitian ini diterima. Ini berarti, ada perbedaan pengaruh terhadap kemampuan menulis siswa di SMA N 4 Singaraja terhadap pengajaran mengunakan teknik Genre-Based Approach dan stategi biasa.keyword : Kemampuan Menulis dan Genre-Based Approach